Improvement in Quality of Life, Pain and Function After Total and Unicompartmental Knee Replacement: A Secondary Analysis of 12-Month Post-Operative Outcomes - Deborah Snell; Jennifer Dunn; Gary Hooper (Advances in Orthopedics)
Conclusions: This study adds to a growing literature showing that knee replacement contributes to substantial improvements in QOL outcomes. Future QOL outcome research in the knee replacement population should consider using more precise measures of function to better understand the impacts of these factors on QOL improvement.